Cardiac abnormalities in children with thalassemia major: correlation of echocardiographic parameters with serum ferritin levels - Shivanna, Niranjan Hunsanahalli; Ramachamdrappa, Rajashekhara Murthy G. R Halli; ., Ambica; Munirathnam, Govindraju (International Journal of Contemporary Pediatrics, 2016)
Background: Thalassemias are a group of inherited disorders of haemoglobin synthesis, with significant morbidity and mortality. The leading cause of death in transfused thalassemia major children is myocardial haemosiderosis. Echocardiographic estimation of left ventricular function may reveal abnormalities before there is any clinical evidence of cardiac disease. The aim of the study was to determine the magnitude and nature of cardiac involvement in children with thalassemia major with respect to various serum ferritin levels. Methods: A prospective study was done on 30 cases of Thalassemia major attending our tertiary referral centre for a period of two yrs. The relationship of blood transfusion and serum ferritin with the parameters PWT-d, PWT-s, LViedd, LViesd, septal thickness, E/A and ES were studied. Results: Out of 30 patients studied, mean age was 4.02 yrs, mean number of transfusions was 28.97 and mean serum ferritin level was 1475. Mean serum ferritin levels of the patients receiving transfusions were estimated in various groups, ferritin levels were higher (2610 ±115.33) in patients who had received more than 50 transfusions.3 of our patients had features of left ventricular hypertrophy in ECG, rest were normal and none of them had evidence of cardiac arrhythmia. Echo parameters were compared; an increase in LViesd was noted in cases when compared to controls which was statistically significant (0.006). Conclusions: Persistent ferritin levels greater than 2500 mcg/ml and assessment of annual blood requirement can assist in prediction of development of cardiac disease. Thus, regular monitoring for cardiac dysfunction and arrhythmias with annual echocardiogram and ECG is extremely important.